Mekanisme Pengelolaan Dana Tabarru’ Asuransi Syariah Prudential Life Assurance - Kambali, Muhammad (JES (Jurnal Ekonomi Syariah), 2017)
Sharia Insurance according to a binding ruling in religious matters (fatwa) of the National Shari'ah Board of the Indonesian Ulama Council no: 21 /DSN-MUI/ X / 2001 is a mutual effort to help among a number of people/parties through investment in assets or tabarru' which provides a pattern of return to face certain risks through engagement in accordance with the sharia. PRUlink sharia is an insurance product associated with sharia-based investment. PRUlink Syariah is designed to meet the society's need for future financial designs in accordance with Islamic principles of sharia. There are two types of product of PRUlink Syariah insurance, namely PRUlink Syariah Investor Account and PRUlink Syariah Assurance Account. Kind of Product in PRUlink Syariah is contract between policy holders using contract of tabarru which is called hibah and the owner of the policy/participant premises sharia insurance company using contract of tijarah called wakalah bin ujrah. In sharia insurance there is a surplus sharing that will be distributed to customers calculated at the end of the calendar year. This can be obtained if there are more funds than tabarru' accounts that have been reduced by claims and debt to the company if any. How is PRUlinksyariah managed in Prudential? The result of the research shows that PRUsyariah premium management in Prudential is separated by two accounts, namely tabarru' account and investment account. The own fund is managed by Eastpring Investment, that is manager company from Asia prudential, while allocation of fund is invested in stocks and obligation which is in accordance with sharia principles contained in the Jakarta Stock Exchange. For the choice of investment in PRUsariah, there are three options of investment, namely Sharia-Rupiah Equity Fund, Sharia-Rupiah Managed Fund or Sharia-Rupiah fixed Income fund, in accordance with the choice of the next participant. From the investment result the participant agrees to pay tabarru’ contribution directly input into tabarru' account. Tabarru’ funds are fully owned by participants and used to pay claims participants claim at any time, but if there is tabaaru’ funds excess with claims total in one year as of 31 December paid, then tabarru’ surplus or that is called surplus will be distributed participants that meet the requirements to get the surplus. Keywords: Tabarru’ Fund Management, Sharia Insurance, Prudential Life